4C Skills (Critical Thinking, Creative, Collaboration, and Communication) in Physics Learning: Have They Been Formated in Students? - Rizaldi, Dedi Riyan; Fatimah, Ziadatul (Balai Publikasi Indonesia, 2024)
One of the skills that are needed by students in current developments is 21st century skills, also known as 4C skills. This study aims to measure and describe the level of 4C skills possessed by students majoring in science at MA Plus Nurul Islam Sekarbela. The type of research used is descriptive-qualitative. The research subjects were all students majoring in science in grades 10–12, totaling 84 students. The research data was gathered using two methods: test questions for critical thinking and creative thinking, and observation sheets for collaboration and communication skills. All data obtained were analyzed descriptively and categorized based on the criteria of each 4C skill. Based on the research, it was found that communication skills were the skills with the highest score for students majoring in science at MA Plus Nurul Islam Sekarbela, with a score of 82.00, while creative thinking was the skill with the lowest score, with a score of 69.00.